AGA112: Propagation Techniques / Faculty of Plantation and Agrotechnology - UiTM, Faculty of plantation and Agrotechnology (Universiti Teknologi MARA (UiTM), 2020)
The course contains principles of plant propagation using seeds, cuttings, grafting, budding, layering, and specialized stem and root. The physiological basis of propagation is described. Knowledge of plant growth and physiology is needed.